Yoga, Meditation and Mental Health Well-Being during Covid-19 Pandemic (Global Journal of Science Frontier Research, 2022)
Yoga and meditation have been playing vital roles in our holistic wellbeing and attaining our spiritual goals since ancient time. During second wave of Covid-19 and lock-down its importance became more significant and visible around the globe. Many patients have easily recovered with the help of their boosted immunity by doing yoga and meditation (like breathing exercise, Bhramari Pranayama and meditation etc) and could keep themselves stress-free. During and post pandemic maintaining mental health is a great challenge. It is very difficult to be relaxed, peaceful and healthy due to increased level of anxiety, stress and depression as a consequence of loss of health, lives, jobs, migration, inaccessibility to health education and other basic facilities, changes in life styles and so on. Yoga can help us to stay calm, manage our health and anxiety without any extra intervention if understood well and made a part of our daily routine. For the young adults it becomes even more important to do yoga and meditation because they are the future of India.
Keywords: yoga; meditation; stress; mental health; ordinal logistic regression analysis